Association between smoking cessation and short‐term health‐care use: results from an international prospective cohort study (ATTEMPT). (14th August 2013) - Beard, Emma; Shahab, Lion; Curry, Susan J.; West, Robert
Abstract Background and aims Previous studies have found that smoking cessation is associated with a short‐term increase in health‐care use. This may be because 'sicker' smokers are more likely to stop smoking. The current study assessed the association between smoking cessation and health‐care use, adjusting for pre‐cessation physical and mental health conditions. Design/setting Data came from the ATTEMPT cohort, a multi‐national prospective survey of smokers in the United States, Canada, United Kingdom, France and Spain, that lasted 18 months (with follow‐ups every 3 months). Participants A total of 3645 smokers completed the baseline questionnaire. All participants smoked at least five cigarettes per day, intended to quit smoking within the next 3 months and were between 35 and 65 years of age. Measurements Participants were asked questions about their socio‐demographic and smoking characteristics, as well previous smoking‐related morbidities. Participants were also asked to report their health‐care use in the previous 3 months i.e. emergency room (ER) visits, hospitalization, whether hospitalization required surgery, and health‐care appointments. Findings A total of 8252, 4779 and 1954 baseline episodes of smoking were available for 3, 6 and 12 months, respectively. Of these, 2.8% (n = 230), 0.9% (n = 40) and 0.7% (n = 14) were followed by 3, 6 and 12 months of abstinence. No significant differences were found among 3, 6 or 12 months of abstinence and ER visits, hospitalization and whether hospitalization required surgery or health‐care visits. However, 6‐month smoking cessation episodes were associated with higher odds of reporting an appointment with a dietician. Conclusion Smoking cessation does not appear to be associated with a substantial short‐term increase or decrease in health‐care use after adjusting for pre‐cessation morbidities.